ANALISIS RASIO UNTUK MENGUKUR KINERJA LAPORAN KEUANGAN PT. GUDANG GARAM TBK YANG GO PUBLIK DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Nur Hidayati; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This study aims to measure the performance of the financial statements of companies that go public the Indonesian Stock Exchange (BEI). The analysis tool liquidity ratio, solvency, and profitability ratios are used to measure the performance of the company’s financial statements. The results showed that the performance of the financial statements. Gudang Garam Tbk during the five year period from 2011 to 2015 fluctuated or unstable.